Revision of the family Murmidiidae (Coleoptera: Coccinelloidea) - Jałoszyński, Paweł; Ślipiński, Adam (Zootaxa, 2022)
The coccinelloid (Cucujiformia) family Murmidiidae is revised. Thirty-four species (including sixteen new) in four genera (incl. one new) are recognized: Botrodus championi Slipinski (Mexico), Botrodus dufaui Grouvelle (Caribbean), Botrodus estriatus Casey (Nearctic, Caribbean), Botrodus montserratensis sp. n. (Caribbean), Murmidius araguanus sp. n. (Venezuela), Murmidius australicus sp. n. (Australia), Murmidius campbelli sp. n. (Colombia, Panama), Murmidius convexus sp. n. (Brazil), Murmidius drakei Heinze (Bolivia, Brazil, Paraguay), Murmidius elongatus sp. n. (Argentina, Brazil), Murmidius globosus Hinton (Chile), Murmidius hawaiianus sp. n. (Hawaiian Islands), Murmidius hebrus Hinton (Afrotropical), Murmidius irregularis Reitter (Guatemala, Mexico), Murmidius lankanus sp. n. (Sri Lanka), Murmidius melon Guerrero, Ramírez & Vidal (Chile), Murmidius meridensis sp. n. (Venezuela), Murmidius merkli sp. n. (India), Murmidius okinawanus sp. n. (Japan: Okinawa Is.), Murmidius ovalis (Beck) (cosmopolitan), Murmidius panamanus sp. n. (Panama), Murmidius rectistriatus Lewis (Mexico), Murmidius segregatus Waterhouse (Mascarene Islands), Murmidius stoicus Hinton (Singapore, Thailand, India, Myanmar, ?China), Murmidius tachiranus sp. n. (Venezuela), Murmidius trujilloensis sp. n. (Venezuela), Murmidius tydeus Hinton (W Malaysia, Singapore), Murmidiella sola gen. & sp. n. (Ecuador), Mychocerinus arizonensis Lawrence & Stephan (USA: Arizona; Mexico: Sonora), Mychocerinus caledonicus sp. n. (New Caledonia), Mychocerinus depressus (LeConte) (eastern USA), Mychocerinus oahuanus sp. n. (Hawaiian Islands), Mychocerinus piceus sp. n. (Argentina), and Mychocerinus pilifer (Lewis) (Guatemala, Mexico). Murmidius chapini Hinton, syn. n. is placed as a junior synonym of Murmidius irregularis Reitter. Detailed morphological structures are described and illustrated for each genus, and identification keys to all treated genera and species are given.